Memorandum of understanding between Universiti Teknologi MARA and Al Madinah International University (MEDIU) / Fakulti Kejuruteraan Awam - Universiti Teknologi MARA, Fakulti Kejuruteraan Awam (Universiti Teknologi MARA (UiTM), 2019)
Memorandum of Understanding on friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thought and personnel exchange.